(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Women are progressively moving into political leadership. Around the globe today, women are accepting appointments to official cabinets, driving political parties, serving on the seats of high courts, and directing security powers. Be that as it may, existing cross-national research on women’s political power overwhelmingly centers around women’s portrayal in national legislatures and official ministries. This paper inspects international relations feminism from the rise of women’s power. We contend that as opposed to feminism being an ongoing development in the field of international relations, it is international relations that has come late to feminism.